2. CLINICAL CHARACTERISTICS OF CASES OF HYSTERECTOMY DURING AND AFTER DELIVERY AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical characteristics of cases of hysterectomy during and after delivery at Hanoi Obstetrics and Gynecology Hospital from January 2019 to December 2023.Materials and methods: A descriptive, cross-sectional, retrospective study on 276 cases of hysterectomy during and after delivery at Hanoi Obstetrics and Gynecology Hospital from January 2019 to December 2023.Results: The rate of hysterectomy during and after delivery accounted for 0.16% of total deliveries. The average age of the subjects was 34.9 ± 4.7 years. Most of the women had a history of giving birth ≥ 2 times, accounting for 73.6% of hysterectomy cases, with the majority having had 2 previous cesarean sections. Most of the women had a history of at least one abortion, curettage, or suction (51.1%). Most of the women underwent cesarean delivery followed by hysterectomy during or immediately after the cesarean, while 23 cases had vaginal delivery followed by hysterectomy post-delivery.Conclusions: A history of multiple births, especially cesarean sections, is a major risk factor for hysterectomy during and after delivery in subsequent pregnancies.
Keywords: Hysterectomy; Hanoi Obstetrics and Gynecology Hospital; cesarean delivery; vaginal delivery